El contexto y el discurso público - Pardo Abril, Neyla Graciela (Enunciación, 2002)
A common place in social sciences is to appeal to the notion of context in order to explain the phenomena of their interest. Thisconcept plays a key role especially in those disciplines that intend to explain and descri- be language and discourse, However, this notion is far from being clearly understood, given the great diversity of viewpoints in this respect, many of which are ignored by researchers of other fields. This article presents a systematic review of the main perspectives on context and their conceptual relationships with the production and understanding of the language in a social group. It is shown that categories such as knowledge, memory, and society, among others, are recurrent in diverse disciplines, and that they are indispensable to elaborate an appropriate notion of context.